TLR8 signaling enhances tumor immunity by preventing tumor‐induced T‐cell senescence. Issue 10 (17th September 2014) - Ye, Jian; Ma, Chunling; Hsueh, Eddy C; Dou, Jie; Mo, Wei; Liu, Shuai; Han, Bing; Huang, Yi; Zhang, Yanping; Varvares, Mark A; Hoft, Daniel F; Peng, Guangyong
Abstract Accumulating evidence suggests the immunosuppressive microenvironments created by malignant tumors represent a major obstacle for effective anti‐tumor immunity. A better understanding of the suppressive mechanisms mediated by tumor microenvironments and the development of strategies to reverse the immune suppression are major challenges for the success of tumor immunotherapy. Here, we report that human tumor cells can induce senescence in naïve/effector T cells, exhibiting potent suppressive function in vitro and in vivo. We further show that tumor‐derived endogenous cyclic adenosine monophosphate (cAMP) is responsible for the induction of T‐cell senescence. Importantly, activation of TLR8 signaling in tumor cells can block the induction and reverse the suppression of senescent naïve and tumor‐specific T cells in vitro and in vivo, resulting in enhanced anti‐tumor immunity. These studies identify a novel mechanism of human tumor‐mediated immune suppression and provide a new strategy to reverse tumor immunosuppressive effects for tumor immunotherapy.